Locoregional Therapy for Hepatic Neuroendocrine Metastases - Bercu, Zachary L.; Mitchell, Jason; Camacho, Juan; Kies, Darren D.; Friedberg, Eric; Martin, Charles; Prologo, J. David (Digestive Disease Interventions, 2017)
Neuroendocrine tumors are a heterogeneous group of malignancies with diverse biological and clinical behavior. Locoregional treatments available for the initial and temporal management of neuroendocrine tumors involving the liver include transarterial embolization, transarterial chemoembolization, selective internal radiotherapy, and ablative techniques. These therapies are best employed as part of a multidisciplinary management team focusing on appropriate histopathology, timing, and individuality of each intervention.
Keywords: hepatic; locoregional; neuroendocrine